2017
DOI: 10.1007/s10653-017-9928-3
|View full text |Cite
|
Sign up to set email alerts
|

Human predisposition to cognitive impairment and its relation with environmental exposure to potentially toxic elements

Abstract: New lines of evidence suggest that less than 10% of neurodegenerative diseases have a strict genetic aetiology and other factors may be prevalent. Environmental exposures to potentially toxic elements appear to be a risk factor for Parkinson's, Alzheimer's and sclerosis diseases. This study proposes a multidisciplinary approach combining neurosciences, psychology and environmental sciences while integrating socio-economic, neuropsychological, environmental and health data. We present the preliminary results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…S4 †), but the differences between indoor and outdoor samples are not signicant. The geology of the area is composed mainly of sandstones and clay deposits, where the two elements tend to be concentrated, 45,85 providing additional support to the natural origin earlier assigned for As. Furthermore, other crustal elements associated with PC3 (Table S3 †) include iron (Fe), Ga, niobium (Nb), and cobalt (Co), which support further the assumption that As and Mo, although enriched (Fig.…”
Section: Source Identication and Apportionmentmentioning
confidence: 66%
See 3 more Smart Citations
“…S4 †), but the differences between indoor and outdoor samples are not signicant. The geology of the area is composed mainly of sandstones and clay deposits, where the two elements tend to be concentrated, 45,85 providing additional support to the natural origin earlier assigned for As. Furthermore, other crustal elements associated with PC3 (Table S3 †) include iron (Fe), Ga, niobium (Nb), and cobalt (Co), which support further the assumption that As and Mo, although enriched (Fig.…”
Section: Source Identication and Apportionmentmentioning
confidence: 66%
“…In the late 1990's the area was remediated and industrial wastes containing hazardous materials such as pyrite ashes, mercury-enriched muds, and organochlorine compounds, were buried and sealed near the complex. Nevertheless, recent studies have been reporting on elevated contents of environmental contaminants in natural media, namely mercury (Hg) in lake sediments, 43 As in soil and groundwater, 44,45 and PM10 in ambient air. 42 In recent years, several studies available from the literature have suggested that currently, vehicular traffic stands for a contributor of increasing importance to the quality degradation of the local environment.…”
Section: The Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…They support agriculture and the main carbon reservoir of the terrestrial carbon cycle, they act as a sink for pollutants, protecting groundwater from pollution, and they are also used as construction material and support. Therefore, they have very important social, environmental, and economic functions [1,2].…”
Section: Introductionmentioning
confidence: 99%